PENGEMBANGAN TEKNOLOGI TEPAT GUNA MESIN PENGAYAK PASIR BERTINGKAT - Awia Conang; Marthina Mini (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Sains dan Teknologi Jayapura, 2014)
Jayapura is a city that is currently a lot of construction everywhere, ranging fromresidential, office, shop - shop and others. The use of sand in constructing a buildingmore and more increasing. Increased use of these sands occur because of the day today needs of the building for economic survival that are needed in everyday life.Practical and economical nature of these causes of sand used as raw materials thatare beneficial for development. The purpose of this study was to develop a simple sandsieving machine is easy to operate for building materials in Jayapura.Method development and research is to design a multi-storey sand sievingmachine using an electric motor. In this study should be planned is the motor powercounting, shafts, pins, bearings, pulleys and belts. After the newly designed tool thathas obtained the appropriate calculations.The results obtained from this study were stratified sand sieving machine isalready done the calculations and the design process so that it can be concluded thatalthough the machine is not as automatic as sieving sand from previous studies, but ithas been well-operated machine that can already be used to sift the sand, in this caseis sand as a building material for construction workers in the city of Jayap